Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.21203/rs.3.rs-477534/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Dry Textile Electrodes for Long-term Electrocardiographic Monitoring

Abstract: Background: Continuous long-term electrocardiography monitoring has been increasingly recognized for early diagnosis and management of different types of cardiovascular diseases. To find an alternative to Ag/AgCl gel electrodes that are improper for this application scenario, many efforts have been undertaken to develop novel flexible dry textile electrodes integrated into the everyday garments. With significant progresses made to address the potential issues (e.g., low signal to noise ratio, high skin-electro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…For a more details, look into the range of frequencies assessed (1, 10, 100, 1 K, and 10 KHz) and please refer to our prior study. 44 During impedance testing, coatings 9 and 10 were found to be abrasive and uncomfortable for the skin. As a result, these coatings did not advance to phase 3.
Figure 5.Mean relative signal-to-noise ratio (rSNR).
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a more details, look into the range of frequencies assessed (1, 10, 100, 1 K, and 10 KHz) and please refer to our prior study. 44 During impedance testing, coatings 9 and 10 were found to be abrasive and uncomfortable for the skin. As a result, these coatings did not advance to phase 3.
Figure 5.Mean relative signal-to-noise ratio (rSNR).
…”
Section: Resultsmentioning
confidence: 99%
“…The process flow detailing material selection for the electrodes in this study can be found in a prior study by the same team, assessing the electrode properties on an agar skin model. 44 Knitted electrodes were tested with and without screen-printed polymer coating. Knitted electrodes were produced using an 18-gauge flatbed knitting machine (CMS-ADF, Stoll, Germany) using either 200 denier silver or 640 denier carbon yarn.…”
Section: Methodsmentioning
confidence: 99%
“…However, low resistance is not the only criteria for an electrode to perform better during ECG signal recording and it is unknown if the ECG signal depends only on low skin-electrode impedance 18,57 . The braided electrodes were mounted on the skin without controlling the adhesion force and might have different skin contact pressure contributing to unwanted noise during ECG recording and differences in SNR was observed.…”
Section: Ecg Analysis and Monitoringmentioning
confidence: 99%